Answer:
P(x)=(x-2)(x-4)(x+3)(x+6)
Explanation:
Given: P(x)=x⁴+3x³-28x²-36x+144
It is a polynomial with degree 4.
It should maximum four factor.
Hit and trial error method.
Put x = 2 into P(x)
P(2)=2⁴+3×2³-28×2²-36×2+144
P(2) = 0
So, x-2 would be factor of P(x)
Now divide x⁴+3x³-28x²-36x+144 by x-2 to get another factors
![(x^4+3x^3-28x^2-36x+144)/ (x-2) = x^3+5x^2-18x-72](https://img.qammunity.org/2020/formulas/mathematics/high-school/zynvghyihqe3uyh6t2dgxjh73uj1f0xt2h.png)
![P(x)=(x-2)(x^3+5x^2-18x-72)](https://img.qammunity.org/2020/formulas/mathematics/high-school/nc7fa1oprujdxy0z4k255xpaoxyioa56ba.png)
Put x = 4
now divide
by x-4
![(x^3+5x^2-18x-72)/ (x-4) = x^2+9x+18](https://img.qammunity.org/2020/formulas/mathematics/high-school/92qyeju0c4hj3z8yxwc4d8pdhisrkl1ee9.png)
![P(x)=(x-2)(x-4)(x^2+9x+18)](https://img.qammunity.org/2020/formulas/mathematics/high-school/qhwubogylz9okl3yofo2v7ouh37hpu0w7h.png)
Now factor
![x^2+9x+18](https://img.qammunity.org/2020/formulas/mathematics/high-school/fvlsxsysjhegbfulzd5hfayth2ava3i02e.png)
Complete factor of P(x)
P(x)=(x-2)(x-4)(x+3)(x+6)